An Early Reading Assessment Battery for Multilingual Learners in Malaysia - Lee, Julia A. C.; Lee, Seungjin; Yusoff, Nur Fatihah Mat; Ong, Puay Hoon; Nordin, Zaimuariffudin Shukri; Winskel, Heather (Frontiers in Psychology, 2020)
The aim of the study was to develop a new comprehensive reading assessment battery for multi-ethnic and multilingual learners in Malaysia. Using this assessment battery, we examined the reliability, validity, and dimensionality of the factors associated with reading difficulties/disabilities in the Malay language, a highly transparent alphabetic orthography. In order to further evaluate the reading assessment battery, we compared results from the assessment battery with those obtained from the Malaysian national screening instrument. In the study, 866 Grade 1 children from multi-ethnic and multilingual backgrounds from 11 government primary schools participated. The reading assessment battery comprised 13 assessments, namely, reading comprehension, spelling, listening comprehension, letter name knowledge, letter name fluency, rapid automatized naming, word reading accuracy, word reading efficiency, oral reading fluency, expressive vocabulary, receptive vocabulary, elision, and phonological memory. High reliability and validity were found for the assessments. An exploratory factor analysis yielded three main constructs: phonological-decoding, sublexical-fluency, and vocabulary-memory. Phonological-decoding was found to be the most reliable construct that distinguished between at-risk and non-at-risk children. Identifying these underlying factors will be useful for detecting children at-risk for developing reading difficulties in the Malay language. In addition, these results highlight the importance of including a range of reading and reading-related measures for the early diagnosis of reading difficulties in this highly transparent orthography.